2015
DOI: 10.1371/journal.pone.0124940
|View full text |Cite
|
Sign up to set email alerts
|

Visual Cycle Modulation as an Approach toward Preservation of Retinal Integrity

Abstract: Increased exposure to blue or visible light, fluctuations in oxygen tension, and the excessive accumulation of toxic retinoid byproducts places a tremendous amount of stress on the retina. Reduction of visual chromophore biosynthesis may be an effective method to reduce the impact of these stressors and preserve retinal integrity. A class of non-retinoid, small molecule compounds that target key proteins of the visual cycle have been developed. The first candidate in this class of compounds, referred to as vis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
52
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(56 citation statements)
references
References 43 publications
(57 reference statements)
0
52
0
1
Order By: Relevance
“…Selective RPE65 inhibitors could be used to eliminate classic visual cycle function in such species and allow detailed examination of the intraretinal visual cycle in isolation. For patients with Stargardt disease wherein A2E is thought to be a primary contributor to macular degeneration (Sparrow and Boulton, 2005;Moiseyev et al, 2010;Charbel Issa et al, 2015;Saad and Washington, 2016), direct RPE65 inhibition by emixustat-like molecules could be therapeutically advantageous, as it was previously reported that both emixustat and its predecessor retinylamine lower A2E formation in mouse models of Stargardt disease (Maeda et al, 2011;Bavik et al, 2015). These compounds also exert beneficial effects in mouse models of diabetic retinopathy thought to be related to their ability to inhibit RPE65 (Liu et al, 2015).…”
Section: Rdh8mentioning
confidence: 98%
See 1 more Smart Citation
“…Selective RPE65 inhibitors could be used to eliminate classic visual cycle function in such species and allow detailed examination of the intraretinal visual cycle in isolation. For patients with Stargardt disease wherein A2E is thought to be a primary contributor to macular degeneration (Sparrow and Boulton, 2005;Moiseyev et al, 2010;Charbel Issa et al, 2015;Saad and Washington, 2016), direct RPE65 inhibition by emixustat-like molecules could be therapeutically advantageous, as it was previously reported that both emixustat and its predecessor retinylamine lower A2E formation in mouse models of Stargardt disease (Maeda et al, 2011;Bavik et al, 2015). These compounds also exert beneficial effects in mouse models of diabetic retinopathy thought to be related to their ability to inhibit RPE65 (Liu et al, 2015).…”
Section: Rdh8mentioning
confidence: 98%
“…This pharmacological concept was realized with the development of retinylamine, a transition state analog of the retinoid isomerization reaction (Golczak et al, 2005). A nonretinoid derivative of retinylamine, emixustat phenyl)propan-1-ol)], was developed later (Bavik et al, 2015), entering clinical trials for the treatment of dry AMD (Kubota et al, 2012(Kubota et al, , 2014. It is currently being evaluated as a treatment of other conditions, including diabetic retinopathy (NCT02753400).…”
Section: Introductionmentioning
confidence: 99%
“…This favors the formation of bisretinoids, such as A2E (8). Reduced bisretinoid levels have been observed in Abca4 −/− mice treated with drugs that lower circulating vitamin A or inhibit enzymes of the visual cycle (28,41,50). Combination drug therapy with both complement modulators and visual cycle inhibitors may be an effective treatment strategy for STGD1 because it targets both pathogenic mechanisms.…”
Section: Accumulation Of Bisretinoid Pigments In the Rpe Of Abca4mentioning
confidence: 99%
“…The first highly selective and potent inhibitor discovered was retinylamine (Golczak et al 2005b). The systematic comparison of different inhibitors has been reported (Maeda et al 2006a) and, based on those results, emixustat was developed by Acucela Inc. (Bavik et al 2015), but human clinical trials have revealed significant side effects (Kubota et al 2012). Finally, recent studies have questioned the mechanism of action of emixustat and suggested that sequestration of all- trans -RAL should be considered as discussed in Section 8.5 (Figure 10 b ) (Zhang et al 2015).…”
Section: Visual Cycle Modulatorsmentioning
confidence: 99%